2002
DOI: 10.1002/ijc.10121.abs
|View full text |Cite
|
Sign up to set email alerts
|

Significance of vascular endothelial growth factor (VEGF)/soluble VEGF receptor‐1 relationship in breast cancer

Abstract: Angiogenesis, the formation of new blood vessels, is controlled by a balance between positive and negative endothelial regulatory factors. Soluble vascular endothelial growth factor receptor-1 (sVEGFR1), a naturally occurring soluble form of VEGFR1, is a negative counterpart of the vascular endothelial growth factor (VEGF) signaling pathway, which has been characterized as one of the most important endothelial regulators in human tumor angiogenesis. In our study, we examined the expression of sVEGFR1 in 110 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 4 publications
(4 reference statements)
1
45
1
2
Order By: Relevance
“…The current study using a highly sensitive sVEGFR-1 ELISA system confirmed that sVEGFR-1 is a significant prognostic indicator. In particular, we discovered that low sVEGFR-1 was related to an unfavourable prognosis, which was a slightly different result from that we had in a previous study with a relatively low-sensitivity sVEGFR-1 ELISA system, where we found a prognostic value of high sVEGFR-1 concentrations for favourable prognosis (Toi et al, 2002). The significance of the ratio of sVEGFR-1 to total VEGF (S/V ratio) as a prognostic marker was reconfirmed in this larger size of analysis.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…The current study using a highly sensitive sVEGFR-1 ELISA system confirmed that sVEGFR-1 is a significant prognostic indicator. In particular, we discovered that low sVEGFR-1 was related to an unfavourable prognosis, which was a slightly different result from that we had in a previous study with a relatively low-sensitivity sVEGFR-1 ELISA system, where we found a prognostic value of high sVEGFR-1 concentrations for favourable prognosis (Toi et al, 2002). The significance of the ratio of sVEGFR-1 to total VEGF (S/V ratio) as a prognostic marker was reconfirmed in this larger size of analysis.…”
Section: Discussioncontrasting
confidence: 94%
“…Kendall et al (1996) found that sVEGFR1 is abundant in all identified VEGFR-1 cDNAs from human primary endothelial cells. In our preliminary study using primary breast cancer tissues, sVEGFR1 was frequently coexpressed with VEGF, and the intratumoral balance between sVEGFR1 and VEGF levels showed a significant relationship with survival (Toi et al, 2002). According to a recent report on brain tumours, the ratio of sVEGFR-1 to VEGF is significantly decreased in glioblastomas compared with astrocytomas, which indicates the importance of sVEGFR-1 expression in brain tumour growth (Lamszus et al, 2003).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…14 The VEGFR-1 sandwich immunoassay used 1 monoclonal anti-human VEGFR-1 antibody and 1 polyclonal antibody. 22,23 …”
Section: Measurement Of Total-vegf-a Free-vegf-a Vegf-c and Vegfr-1mentioning
confidence: 99%